Motives for social media usage on emergency communication an exploratory study in the 2017 flood in New Matina, Gravahan Purok I - Pagtaconan, Joveguel H.; Perez, Teody Boylie R. (2018)
This study was conducted to identify the motivations of the flooded-affected residents of New Matina Gravahan, Purok I in regards to their Social Media Usage on Emergency Communication. It explored the respondents? Social Media Usage, Socio-demographics, and various motivations that would match their drive to utilize Social Media. With Uses and Gratifications Theory as the guide framework, the identified motivations were evaluated as to how they gratify one?s need to use SM in times of disaster. The research revealed the motivations of people in using Social Media in the three phases of flood: pre, during, and post. It also proved that people?s motivations to use Social media vary depending on the circumstances involved. The results gave comparison between Social Media Usage on past flood incidents and on the 2017 Flood. Also, their motivations were tested to be correlated with their socio-demographics. This study is an addition to the several communications researches in regards to Emergency Communication during disasters. However, using Uses and Gratifications Theory in this kind of study is an exploration since it is not commonly uses as such. This will aid further studies in regards to emergency communication in the long run
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2018